STUDI NUMERIK HIDRODINAMIKA UNDERSEA KITE - Mochamad Ganesha (2022)
This research focuses on the study of the tethered undersea kite (TUSK) system for power generation. An underwater tethered kite system consists of rigid wings that move in a flyway or figure-8 below the surface. The tether can be connected to a surface mounted platform or tethered to the ocean floor. In the kite there is a turbine that extracts energy from the forward motion of the kite, which may be utilized by renewable energy potential. The ANSYS fluid dynamics (CFD) software is fluent in channel blocking forces tethered to the seabed. Varying Blades with NACA 0005 which has an angle of attack of 0,7,14,21,28,35 which is simulated at a constant speed of 0.2 rad/s for 1 second which will produce a force that can be used to generate electricity.